Upregulation of photosynthesis in mineral nutrition-deficient tomato plants by reduced source-to-sink ratio - Glanz-Idan, Noga (Plant Signal Behav, 2020)
Photosynthetic activity is affected by environmental factors and endogenous signals controlled by the source–sink relationship. We recently showed upregulated photosynthetic rate following partial defoliation under favorable environmental conditions. Here, we examined the influence of partial defoliation on the remaining leaves’ function in tomato plants under nutrient deficiency. The effect of partial defoliation was more pronounced under limited mineral supply vs. favorable conditions. Reduced source–sink ratio resulted in increased stomatal conductance and transpiration rate, as well as higher photosystem II efficiency. Although chlorophyll concentration was significantly reduced under limited nutrient supply, the photosynthetic rate in the remaining leaf was similar to that measured under normal fertilization. Expression of genes involved in the phloem loading of assimilated sugars was downregulated in the remaining source leaf of unfertilized plants, 15 d after partial defoliation; in fertilized plants, these genes’ expression was similar in control and partially defoliated plants. We propose that at early stage, the additional carbon assimilated in the remaining leaf is devoted to increasing source size rather than sink growth. The size increase of the remaining leaf in unfertilized plants was not sufficient to rebalance the source–sink ratio, resulting in inhibited sugar export and further carbohydrate allocation in the remaining leaf.